2021
DOI: 10.1007/s40820-021-00602-w
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Two-Dimensional Perovskite Solar Cells Realized by Incorporation of Ti3C2Tx MXene as Nano-Dopants

Abstract: Two-dimensional (2D) perovskites solar cells (PSCs) have attracted considerable attention owing to their excellent stability against humidity; however, some imperfectness of 2D perovskites, such as poor crystallinity, disordered orientation, and inferior charge transport still limit the power conversion efficiency (PCE) of 2D PSCs. In this work, 2D Ti3C2Tx MXene nanosheets with high electrical conductivity and mobility were employed as a nanosized additive to prepare 2D Ruddlesden–Popper perovskite films. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 57 publications
(49 reference statements)
2
31
0
Order By: Relevance
“…The X-ray diffraction (XRD) results ( Figure 1 a) showed that two main peaks appeared at 14.28° and 28.58° for all 2D perovskite films, corresponding to the (111) and (202) plane [ 3 ]. The ratio of (111) and (202) peak intensity (I(111)/I(202)) has a relationship to the crystallographic orientations of 2D perovskite [ 20 ]. The smaller ratio meant that the 2D perovskite grew along the vertical orientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray diffraction (XRD) results ( Figure 1 a) showed that two main peaks appeared at 14.28° and 28.58° for all 2D perovskite films, corresponding to the (111) and (202) plane [ 3 ]. The ratio of (111) and (202) peak intensity (I(111)/I(202)) has a relationship to the crystallographic orientations of 2D perovskite [ 20 ]. The smaller ratio meant that the 2D perovskite grew along the vertical orientation.…”
Section: Resultsmentioning
confidence: 99%
“…In order to explore the photophysical properties of 2D perovskite based on different solvents, UV visible (UV–Vis) absorption and photoluminescence (PL) spectroscopy tests were used, as shown in Figure 1 b,c. There were four main absorption peaks at 567 nm, 598 nm, 634 nm, and 750 nm in the UV–Vis absorption spectrum, which represented the perovskite phase with n = 2, 3, 4 and ∞ [ 20 ]. This meant that 2D perovskites based on different solvents had the same structure.…”
Section: Resultsmentioning
confidence: 99%
“…To further improve the long-term operation stability, 2D Ruddlesden-Popper PVSK solar cells have recently been proposed. As shown in Figure 17j, Jin et al [165] reported PVSK solar cells with Ti 3 C 2 T X MXene-doped PVSK flakes; owing to high electrical mobility and conductivity, the current density of the device has been almost linear to the incident light intensity (Figure 17k), suggesting a lower bimolecular recombination degree caused by the reduction in the trap density via introducing MXene as a dopant. Figure 17l demonstrates the stability of the device wherein it is seen that with Ti 3 C 2 T X doped PVSK flakes, the device environmental stability is much better than that of pure PVSK flakes, mostly attributing to a better passivation effect and the crystallinity of PVSK flakes.…”
Section: Perovskite-based Solar Cellsmentioning
confidence: 97%
“…Jin et al, introduced 2D Ti 3 C 2 T x MXene nanosheets as nanosized additives in 2D Ruddlesden-Popper PSCs. Thanks to the enhanced crystallinity, optimized orientation, lower charge transfer resistance and passivated trap states, the PCE, V OC , J SC and FF of 2D PSCs increased from 13.69%, 1.09 V, 18.84 mA cm −2 , and 66.7% (control device without any MXene additive) to 15.71%, 1.11 V, 20.87 mA cm −2 and 67.84%, respectively [ 73 ].…”
Section: Applications Of Mxenes In Pscsmentioning
confidence: 99%